The impact of food price shocks on consumption and nutritional patterns of urban Mexican households - Miriam Juárez Torres (Banco de México, 2015)
– During the 2000s, recurrent food price shocks due to volatility in international markets and extreme weather events affected consumption and nutritional patterns of Mexican urban households. This research quantifies the impacts of food price shocks on the purchase of nutrients and on the weight gain of children in urban Mexican households. We find differentiated patterns of food consumption across income quintiles, which result in heterogeneous effects of price shocks on the purchase of nutrients and on weight gain according to age and sex in children. In particular, cereal price shocks are more detrimental and more regressive than price shocks on other categories like meats or beverages.
Keywords: D12; C31; O12; 330; Food price elasticities; Nutrient elasticities; Food security; Nutrition; Welfare